Nutrient and health benefit of GM rice: a review / Mohamad Muizzuddin Mohd Asri and Hamizah Othman - Mohd Asri, Mohamad Muizzuddin; Othman, Hamizah (Faculty of Plantation and Agrotechnology, 2018)
Oryza sativa is one of the world’s valuable crops which become staple food crop for more than 60 per cent of the people in the world. Moreover, rice becomes problem among people where rice is become their staple food but it is low in macronutrients that required for daily diet. The objective of this review is to review on potential benefit of GM rice and to verify that GM rice can fulfil recommended levels of daily dietary nutrient by human. Improvement on biofortified can be done through genetic engineering and conventional breeding. But. use of genetic engineering made it possible to transfer gene of interest from wild relatives and distinct species that is practicable compared to conventional breeding. Genetic engineering used to ensure plant food get all of micronutrient content to fulfil human needs. Many approaches used to improve multiple GM rice nutrient such as improve amino acid, vitamin A, folate and iron accumulation. However, use of genetic engineering has triggered controversial and further research is also needed to get better understanding about this technology and its role in food security. Potential risk of GM rice to human health also concerned to ensure they are not involved to danger when consume GM rice in their daily life. From this review. GM rice seems like does not show a good future and there is a possibility that this research will not being continue. Then, current scientific advances need to be continued along with the campaign and promotion to provide a better understanding among consumers and also to encourage consumers to participate in review or research to receive GM rice products. GM food should be environmental friendly and safe for human intake and need more assessment before supplied to general.